ENGLISH LANGUAGE TEACHING IN PESANTREN IN INDONESIA: DEVELOPMENT AND CHALLENGES - Umar Umar (STIBA IEC JAKARTA, 2022)
Pesantren is a traditional Islamic educational institution that studies religious knowledge (tafaqquh fi al-dîn) with an emphasis on moral formation of students so that they can practice it with the guidance of kiai and make the kitab kuning book as the primary source and the mosque as the center of activity. The growth of Pesantren as a traditional Islamic boarding school in the urban area has demonstrated that there have been changes in the pesantren itself. However, its existence has not been influenced by sociopolitical, economical, or cultural changes, it does not mean Pesantren does not face problems and challenges externally or internally. This article will talk about some issues such as the development of Pesantren: historical point of view, Pondok Pesantren today and of course the challenges which are occurring around.